Mechanism of HBx carcinogenesis interaction with non-coding RNA in hepatocellular carcinoma - Wang, Zhuoran; Li, Nan; Cai, Peng; Zhang, Cunzhen; Cao, Guangwen; Yin, Jianhua (Frontiers in Oncology, 2023)
Hepatocellular carcinoma (HCC) is an extremely malignant tumor that affects individuals throughout the world. One of the main causes of HCC is hepatitis B virus (HBV). Therefore, it is crucial to understand the mechanisms underlying HBV carcinogenesis. Increasing evidence suggests that the HBV X protein (HBx), which is encoded by HBV, plays a significant role in cell apoptosis, DNA damage repair, and cell cycle regulation. This ultimately leads to the development of HCC. Additionally, recent studies have shown that non-coding RNA (ncRNA) also contributes to the carcinogenesis and pathogenesis of different of tumors. ncRNA plays a significant role in the formation if HCC by regulating the inflammatory signaling pathway, activating immune cells, and modifying epigenetics. However, it remains unclear whether ncRNA is involved in the regulation of the carcinogenic mechanisms of HBx. This article reviews the carcinogenic mechanism of HBx and its interaction with ncRNA, providing a novel strategy for the clinical diagnosis and treatment of HCC.